2016
DOI: 10.1039/c5ra22748h
|View full text |Cite
|
Sign up to set email alerts
|

Nisin anchored cellulose nanofibers for long term antimicrobial active food packaging

Abstract: Increasing consumer demand for high performance bio-based materials in order to develop microbiologically safer foods has forced the food industry to revise their packaging strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 51 publications
2
50
0
1
Order By: Relevance
“…Different strategies for the conjugation or grafting of antimicrobial compounds on CNF have been described in the literature but their efficacy is closely connected to the active molecule (aminosilanes, antibiotics, bacteriocins, etc.). 17,23,37 The set-up of the CNF-sakacin-A active materials was found effective in reducing Listeria population in samples of smoked salmon of about 3 Log cycles with respect to the values reached without or with CNF-only samples after 28 days of storage. In the applied conditions, the bacteriocin concentration in mats was around 50 AU cm −2 .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Different strategies for the conjugation or grafting of antimicrobial compounds on CNF have been described in the literature but their efficacy is closely connected to the active molecule (aminosilanes, antibiotics, bacteriocins, etc.). 17,23,37 The set-up of the CNF-sakacin-A active materials was found effective in reducing Listeria population in samples of smoked salmon of about 3 Log cycles with respect to the values reached without or with CNF-only samples after 28 days of storage. In the applied conditions, the bacteriocin concentration in mats was around 50 AU cm −2 .…”
Section: Discussionmentioning
confidence: 93%
“…Barbiroli et al reported the possibility of incorporating lysozyme and lactoferrin into paper containing carboxymethyl cellulose, that allowed non‐covalent binding of the positively charged proteins to the paper matrix; tests on thin cuts of raw meat also confirmed their antimicrobial effect. Saini et al developed a novel antimicrobial film with covalently linked nisin on surface of TEMPO oxidized cellulose nanofibers for food packaging. Espitia et al studied the effects of pediocin incorporation into a cellulosic packaging produced with cellulose acetate resin, determining the tensile strength at break (in MPa), load at break (in newtons) and elongation at break (%), water vapor permeability and structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their studies on developing an antimicrobial active packaging film, Riaz et al (2018) Many authors developed antimicrobial active packaging with the use of nisin. Nisin has already been used as an antibacterial agent in food products for the past few decades and also has been approved by the European food safety authority within acceptable uptake (Saini, Sillard, Belgacem, & Bras, 2016). Nisin is a bacteriocin and an antimicrobial peptide with 34 amino acids and a molecular weight of 3.5 kDa, produced by strains of Lactococus lactissubsp.…”
Section: Antimicrobial Packagingmentioning
confidence: 99%